Wild blue media : thinking through seawater - Jue, Melody (Durham : Duke University Press, 2020)
"Wild Blue Media: Thinking Through Seawater shows how the conditions of perception in oceanic environments offer new perspectives on media and language"--
Thinking through Seawater -- Interface: Diving the Interface -- Inscription: Vampire Squid Media -- Database: Proteus and the Digital -- Underwater Museums.
Includes bibliographical references (pages [193]-207) and index.
Keywords: Seawater; Technological innovations; Ocean engineering